Eriophyoid mites from Hainan Province, China I: Descriptions of three new species (Acari: Eriophyoidea) - Cheng, Li-Sheng; Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2009)
Three new species of eriophyoid mites from China’s Hainan Island are described and illustrated. They are Epitrimerus danzhouicus sp. nov. on Ficus gibbosa (Moraceae), Epitrimerus dioscoreaepersimilis sp. nov. on Dioscorea persimilis (Dioscoreaceae), Tegolophus liangyuanicus sp. nov. on Litchi chinensis (Sapindaceae). All the eriophyoid mite species described here are vagrants on the undersurface of host leaves.